Microstructure and plasma corrosion behavior of yttria coatings prepared by the aerosol deposition method - Ashizawa, Hiroaki; Masakatsu, Kiyohara; Yoshida, Katsumi (Journal of the American Ceramic Society, 2020)
Particle contamination arising from inner ceramic components of the plasma etching equipment has become a serious issue. Yttria (Y2O3) coatings prepared via aerosol deposition (AD) have demonstrated superior plasma resistance in the reduction of particle contamination. The superior particle contamination performance of Y2O3 coatings prepared by AD has been speculatively attributed to its unique microstructure; however, the relationship between the coatings’ microstructure and plasma corrosion behavior has been insufficiently clarified. Herein, we investigated the relationship between the microstructure and plasma corrosion behavior of Y2O3 coatings prepared by the AD method and compared the results with those for coatings prepared by other coating methods. When internal pores are present, these internal pores were selectively plasma corroded; plasma corrosion marks reflecting their pore shape were formed, and the surface roughness increased with increasing plasma exposure time. However, when no internal pores were present, as in the case of the AD coating, the surfaces were homogeneously corroded and maintained their initial surface. As the risk of particle contamination caused by the corrosion of the plasma‐resistant coatings is greatly increased with surface roughness, we concluded that the Y2O3 coating prepared via AD will contribute greatly to reducing particle contamination.